2017
DOI: 10.1097/md.0000000000006574
|View full text |Cite|
|
Sign up to set email alerts
|

Is rotavirus still a major cause for diarrheal illness in hospitalized pediatric patients after rotavirus vaccine introduction in the Saudi national immunization program?

Abstract: Previous studies in Jeddah, western Saudi Arabia, showed rotavirus (RV) prevalence around 40% in pediatric inpatients with gastroenteritis (GE) with a maximum level during cooler months. Currently, there are no data on impact of rotavirus vaccine (RVV) on RV-GE in Saudi Arabia. Therefore, this study was conducted to assess impact of RVV on incidence and severity of RV-GE in hospitalized pediatric patients; 3 years after introduction of RVV in Saudi immunization program (SIP) in January, 2013.This cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
5
4
0
Order By: Relevance
“…The number of rotavirus infections was lowest in patients <3 months of age, presumably because of the presence of maternal antibodies from breastfeeding. As found in our study, male patients have been reported as more likely to be affected with rotavirus acute gastroenteritis [57][58][59]. Similar to the findings in the countries of the Indian subcontinent [11,34], the G12 detected in Sabah were in combination with P [6].…”
Section: Plos Onesupporting
confidence: 89%
“…The number of rotavirus infections was lowest in patients <3 months of age, presumably because of the presence of maternal antibodies from breastfeeding. As found in our study, male patients have been reported as more likely to be affected with rotavirus acute gastroenteritis [57][58][59]. Similar to the findings in the countries of the Indian subcontinent [11,34], the G12 detected in Sabah were in combination with P [6].…”
Section: Plos Onesupporting
confidence: 89%
“…This study provides evidence of reductions in diarrhoea among both unvaccinated children and adults in a middle-income setting. Other studies illustrating this are mostly in high-income countries (HIC) including Saudi Arabia [29] , the USA [ 30 , 31 ]. In poorer countries this is rare but has been reported, eg.…”
Section: Discussionmentioning
confidence: 99%
“…Attention is therefore being drawn to other enteropathogens in addition to rotavirus. Although rotavirus is still the commonest cause of severe dehydrating diarrhea in underfive children, accounting for about 40% [14][15][16][17] of cases, other pathogens (like Norovirus, E-Coli, Shigella, Campylobacter, Gardia lamblia, etc.) still contribute significantly to morbidity and mortality.…”
Section: The Rotavirus Surveillance Expansionmentioning
confidence: 99%